2019
DOI: 10.1136/bmjresp-2018-000308
|View full text |Cite|
|
Sign up to set email alerts
|

Cell therapy for ARDS: efficacy of endobronchial versus intravenous administration and biodistribution of MAPCs in a large animal model

Abstract: IntroductionBone marrow-derived multipotent adult progenitor cells (MAPCs) are adult allogeneic adherent stem cells currently investigated clinically for use in acute respiratory distress syndrome (ARDS). To date, there is no agreement on which is the best method for stem cells delivery in ARDS. Here, we compared the efficacy of two different methods of administration and biodistribution of MAPC for the treatment of ARDS in a sheep model.MethodsMAPC were labelled with [18F] fluoro-29-deoxy-D-glucose and delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…Also, MSCs can reduce the concentrations of pro-inflammatory cytokines like IL1α, TNFα, IL6, IL12, and IFNγ, and therefore limiting the formation of cytokine storm [40,41]. Studies show the effects of MSCs in the treatment of acute lung injury and chronic lung disease [42]. A previous study found that MSCs can help to attenuate acute lung injury and ischemia-reperfusion mediated lung injury caused by lipopolysaccharide [43].…”
Section: Mscsmentioning
confidence: 99%
“…Also, MSCs can reduce the concentrations of pro-inflammatory cytokines like IL1α, TNFα, IL6, IL12, and IFNγ, and therefore limiting the formation of cytokine storm [40,41]. Studies show the effects of MSCs in the treatment of acute lung injury and chronic lung disease [42]. A previous study found that MSCs can help to attenuate acute lung injury and ischemia-reperfusion mediated lung injury caused by lipopolysaccharide [43].…”
Section: Mscsmentioning
confidence: 99%
“…MSC therapeutic effectiveness is likely limited to a niche of immunological disorders and immune-mediated illnesses such as graft-versus-host-disease, for which MSCs have demonstrated varying levels of efficacy in Phase 1/2 clinical studies 31 , 32 . In multiple pre-clinical studies, MSCs have been shown to be effective against ARDS and acute lung injury (ALI) 33 , 34 , both of which are severe clinical manifestations of COVID-19, and while, administration of MSCs to subjects with ARDS was well tolerated 35 , 36 , efficacy data at the clinical level is not as compelling. To date, there are about 40 clinical trials registered on clinicaltrials.gov for evaluating the use of MSCs in subjects with COVID-19 (Table 1 ) 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment has been followed by a reduction in inflammatory parameters (CRP, ferritin, LDH, IL-6) as well as increase in B-lymphocytes (67%) and CD4 + and CD8 + (100%) T lymphocytes). Remarkably, a reduction of D-dimer and fibrinogen 5 days after the first dose of AT-MSCs has been observed in most patients, and the patients do not develop a thromboembolic event [ 169 , 170 ].…”
Section: Msc Clinical Trials For Covid-19 Patientsmentioning
confidence: 99%